Multi-purpose remote ac device controller / Muhammad Ilman Danish Mohd Hanafi - Mohd Hanafi, Muhammad Ilman Danish (2023)
The Multi-purpose Remote AC Device Controller project aims to modernize the way people use and control their AC devices by utilizing advanced technology. At its core is the ESP32 microcontroller, which connects to an IoT-enabled web interface, an IR sensor, a touch sensor, and a potentiometer. With these components working together, users have better ways to manage and automate their AC devices. Using the potentiometer, people can determine how long they want their AC devices to run. If someone is moving around, the built-in IR sensor will instruct the AC devices to turn on after a set time. However, if someone moves away from the sensor, the AC devices will start a timer to switch off, ensuring they run only when needed. Additionally, there is a quick way to turn everything off using the touch sensor. The objective of this project is to develop a working prototype of a multipurpose remote AC device controller using an ESP32 microcontroller, with inputs such as an IR and touch sensor, a potentiometer, and mobile devices. The outputs will include an OLED display, a relay, and AC devices, allowing for control of the AC devices via IoT by connecting the ESP32 to a web-based platform. This innovative solution has a broad impact across various domains. Environmentally, it promotes energy conservation by managing AC device operations, thereby reducing energy waste. Socially, it enhances user comfort by ensuring that AC devices work based on real movements, promoting a more eco-friendly and comfortable living space. In the industry, this project opens doors for more smart home devices to connect to the internet, demonstrating progress in making homes smarter. In simple terms, this project combines smart technology, energy savings, and user-centric design to pave the way for a future that is both tech-savvy and eco-friendly.